The genus Ancyronyx Erichson, 1847 (Coleoptera, Elmidae) in Palawan and Busuanga, (Philippines) with descriptions of six new species - Freitag, Hendrik; Jäch, Manfred A. (Zootaxa, 2007)
The species of the elmid genus Ancyronyx Erichson from the Philippine islands of Palawan and Busuanga are revised. Six new species are described: Ancyronyx helgeschneideri Freitag & Jäch sp. n., A. minerva Freitag & Jäch sp. n., A. minutulus Freitag & Jäch sp. n., A. patrolus Freitag & Jäch sp. n., A. pseudopatrolus Freitag & Jäch sp. n., and A. punkti Freitag & Jäch sp. n. A checklist and a key to the species of Ancyronyx recorded from the Philippines are provided.